The Effects of Foreign Owned Firms on the Labor Market - Rita K. Almeida (Institute for the Study of Labor (IZA), 2003)
Cross sectional evidence shows that foreign firms have a more educated workforce and pay higher wages than domestic firms. These results do not necessarily imply that foreign direct investment translates into higher demand for educated workers or higher wages, however, since foreign investment may be guided by unobservable firm-characteristics correlated with the demand for educated workers or wages. Using firm-level panel data for Portugal, I seek to isolate the effect of foreign direct investment on the demand for educated workers and wages by observing labor demand and wages of different education groups before and after the foreign acquisition. I find that foreigners 'cherry pick' domestic firms to be acquired, choosing those firms with a more educated workforce. Moreover, these firms are already very similar to the group of existing foreign firms and, following the foreign acquisition, there are no significant changes in the workforce educational composition. There is evidence that average wages increase following the foreign acquisition but changes are smaller than in cross sectional estimates.
Keywords: F23; C31; J31; 330; foreign direct investment; acquisitions; employment and wage structure; Direktinvestition; Übernahme; Multinationales Unternehmen; Arbeitsnachfrage; Facharbeiter; Qualifikation; Lohnstruktur; Schätzung; Portugal